The Surrealism of Men’s Rights Discourses on Sexual Assault Allegations: A Feminist Reading of Kafka’s The Trial - Lonergan, Meg Danielle (Atlantis)

(untitled) (Mount Saint Vincent University, 2018)
Being a feminist in the contemporary Canadian context, post-Ghomeshi, can lead to existential crises. In this paper I investigate this relationship of feminist activism and reality, men’s rights activism (MRA) and surrealism, and the Absurd via the work of surrealist novelist Franz Kafka. While Kafka’s The Trial is popularly understood as an allegory for the alienation and pains of bureaucracy and modernity, I posit a new interpretation of the story as a men’s rights perspective of sexual assault allegations. I use Shoshana Felman’s theory of integrated literary and legal visions to read Kafka’s The Trial against men’s rights discourses regarding sexual assault allegations. I find this theory of evidence and repetitions across the disciplines of art (Kafka) and law (the Ghomeshi trial) useful as analytical sites for critically engaging with men’s rights discourses about sexual assault allegations. I demonstrate how The Trial can be interpreted as a representation of the phenomenon of sexual assault allegations according to men’s rights discourses, and demonstrate how these discourses are just as surreal as Kafka’s story. Through the Ghomeshi verdict I will demonstrate how these surrealist fantasies impact real-world sexual assault accusations, trials, and court decisions.